Penerapan Teori Keagenan Dalam Analisis Kinerja Keuangan Daerah Terhadap Belanja Modal Untuk Pelayanan Publik - Urip Wardoyo, Dwi; Nursadrina, Athirah; Pungky Susanta, Christina; Puspita, Rima (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to measure financial performance based on the analysis ratio of finance to capital expenditure in the West Java region in 2021. The test was conducted in 27 counties/cities of West Java using quantitative analysis with simple regression. Financial performance analysis using the independence ratio calculation, effectiveness, and efficiency. Capital expenditures for public services are Measured utilizing the amount of capital expenditure for public services in the budget. The results showed that the independence and effectiveness ratios significantly positively affect capital spending for public services in counties/cities of West Java. Therefore, local governments are expected to prioritize local government financial performance to increase local capital expenditures